Gender roles in tourism development in East Nusa Tenggara -Timor Leste border - Nalle, Frederic Winston; Muljaningsih, Sri (Goodwood Publishing, 2024)
Purpose: This research explores the challenges and opportunities of integrating a gender perspective into tourism development in the border regions of East Nusa Tenggara (ENT) and Timor Leste. Research Methodology: Using a qualitative approach, this study collected data through literature reviews and stakeholder interviews. Results: The analysis revealed that women face various obstacles to tourism sector development, such as limited access to capital, unequal job opportunities, and societal gender stereotypes. Despite these challenges, there are significant opportunities for women to enhance their participation in the tourism industry, potentially leading to increased wellbeing. Conclusions: This study emphasizes the need for a gender-inclusive approach in the tourism sector of East Nusa Tenggara and Timor Leste to promote sustainable economic development. Empowering women and addressing cultural barriers are essential for creating an inclusive tourism model that benefits local communities. Limitations: This study acknowledges limitations, including the scope of qualitative research and the challenges in generalizing findings to broader contexts beyond ENT and Timor Leste. Contributions: Based on these findings, this research proposes tourism development strategies focusing on inclusive gender vocational training programs; enhanced collaboration among government, private sector, and educational institutions; and promoting women's leadership and decision-making roles in tourism management. Novelty: This study highlights the potential for more inclusive tourism development in the ENT-Timor Leste border region, with the aim of providing economic benefits to local communities.